2015
DOI: 10.3341/kjo.2015.29.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Combined Cataract Extraction and Vitrectomy for Macula-sparing Retinal Detachment: Visual Outcomes and Complications

Abstract: PurposeTo evaluate the visual outcome of combined phacoemulsification, intraocular lens implantation, and vitrectomy for macula-sparing rhegmatogenous retinal detachment.MethodsThe results of combined vitrectomy with cataract extraction were retrospectively analyzed in patients with preexisting cataracts and new-onset rhegmatogenous retinal detachment. To qualify, patients must also have had macular sparing in a region 6,000 µm in diameter on optical coherence tomography. The anatomical success rate, visual ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…32 Kim et al performed a retrospective study involving 56 phakic patients with macula-sparing RD undergoing phacovitrectomy, which showed a 100% final surgical success rate for reattachment. 33 In 35.7% of patients, however, the postoperative visual acuity was worse than the preoperative visual acuity owing to ERM development (10.7%), posterior capsular opacification (21.4%) and CMO (3.6%). 33 In 2021, Tan et al demonstrated that eyes undergoing phacovitrectomy and PPV alone had an anatomic success rate of 84.3% and 89.2%, respectively.…”
Section: Retinal Detachmentmentioning
confidence: 88%
See 1 more Smart Citation
“…32 Kim et al performed a retrospective study involving 56 phakic patients with macula-sparing RD undergoing phacovitrectomy, which showed a 100% final surgical success rate for reattachment. 33 In 35.7% of patients, however, the postoperative visual acuity was worse than the preoperative visual acuity owing to ERM development (10.7%), posterior capsular opacification (21.4%) and CMO (3.6%). 33 In 2021, Tan et al demonstrated that eyes undergoing phacovitrectomy and PPV alone had an anatomic success rate of 84.3% and 89.2%, respectively.…”
Section: Retinal Detachmentmentioning
confidence: 88%
“…33 In 35.7% of patients, however, the postoperative visual acuity was worse than the preoperative visual acuity owing to ERM development (10.7%), posterior capsular opacification (21.4%) and CMO (3.6%). 33 In 2021, Tan et al demonstrated that eyes undergoing phacovitrectomy and PPV alone had an anatomic success rate of 84.3% and 89.2%, respectively. 34 Despite good anatomic outcomes in cases of combined phacovitrectomy, visual outcomes may be limited by postoperative myopic surprise due to difficulty obtaining accurate, high-quality lens calculations.…”
Section: Retinal Detachmentmentioning
confidence: 88%
“…In addition to an extra corneal incision, the intracameral approach could result in further iris trauma and pupil miosis and instability of anterior chamber, especially when using contact lenses visualization systems. [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%